THE STATE OF LINGUISTIC THINKING - Каримжанова Ёкутхон Уринбаевна (Ecomind Press, 2025)
Today, the main focus is on studying the social, psychological, psycholinguistic and philological features of language from a scientific point of view. This article examines changes in language and thinking related to social processes in the development of society, as well as their psychological and linguistic features. Inventions without reference to the development of society, a new concept, and an increase in the number of new words are a natural process. The specific changes in him, the improvement of thinking and language are undeniable. The article describes the study of these issues in the field of psycholinguistics.
Keywords: Psycholinguistics, language, speech activity, lexicon, thinking, speech, ontogenesis, communication, imagination.